Orthorexia Nervosa and Quality of Life in an Austrian Sample of Young Adults – An Exploratory Study - Verena Steiner-Hofbauer; Gloria Mittmann; Syliva Dörfler; Beate Schrank (International Journal of Nutrition, 2023)
Young adulthood is a sensitive phase that comes with many developmental tasks. Successful mastery of these challenges is crucial not only for long-term physical and mental health. A positive relationship with one's own body and associated healthy dietary and behavioral patterns are essential building blocks for healthy adolescence and adult life. But being overly concerned with healthy food may lead to decreased quality of life and negative (mental) health outcomes. This study was conducted via a cross-sectional online questionnaire including the Düsseldorfer Orthorexieskala(DOS), the WHO Quality of Life BREF and questions about life style and nutritional habits. We investigated the prevalence of ON and its relationship with different aspects of quality of life and lifestyle factors (sport and nu trtional habits) in a sample of young adults in Austria. No significant difference in the DOS-scores of male and female participants were found and no significant difference between students and non-students. High DOS-scores significantly impair all three domains of QoL. We did not find a significant relationship between high DOS-scores and taking nutritional supplements or being vegan, vegetarian or omnivore. Participants with high DOS-scores spent significantly more hours per week with sport/exercising.
Keywords: Orthorexia Nervosa